Endurance : Shackleton's incredible voyage - Lansing, Alfred (New York : Caroll & Graf, 1999)
The astonishing saga of polar explorer Ernest Schackleton's survival for over a year on the ice-bound Antarctic seas, as "Time" magazine put it, "defined heroism". Alfred Lansing's scrupulously researched and brilliantly narrated book--with over 200,000 copies sold--has long been acknowledged as the definitive account of the "Endurance's" fateful trip.
Originally published: New York : McGraw-Hill, 1959. With new maps and illustrations.
Keywords: Shackleton, Ernest Henry, -- Sir, -- 1874-1922 -- Travel -- Antarctic regions; Endurance (Ship); Antarctica -- Discovery and exploration